Odpowiedź:
zad15
a)[tex]\frac{8\sqrt{3} }{2\sqrt{3} } =4[/tex]
b)8√7+3√7=11√7
c)5∛6+∛6+∛-6=6∛6-∛6=5∛6
zad16
a)3(√7)²=3*7=21
b)[tex]2\sqrt{8} *3\sqrt{8} =6\sqrt{8*8} =6*8=48[/tex]
c)[tex](\frac{3}{4} \sqrt{6} )^2=\frac{9}{16} *6=\frac{27}{8} =3\frac{3}{8}[/tex]
zad17
a)[tex]\sqrt{64} -\sqrt[3]{-125} =8-(-5)=8+5=13[/tex]
b)[tex]3\sqrt{\frac{1}{25} } +\frac{\sqrt{36} }{3} =3*\frac{1}{5} +\frac{6}{3} =\frac{3}{5} +2=2\frac{3}{5}[/tex]
c)[tex]\sqrt{100} -\sqrt{64} +\sqrt{100-64} =10-8+\sqrt{36} =2+6=8[/tex]
d)[tex]\sqrt{900} :\sqrt[3]{8} +\sqrt{81} =30:2+9=15+9=24[/tex]
zad18
[tex]\sqrt{2\frac{1}{4} } *2^3-(\frac{1}{2} )^2=\sqrt{\frac{9}{4} } *8-\frac{1}{4} =\frac{3}{2} *8-\frac{1}{4} =12-\frac{1}{4} =11\frac{3}{4}[/tex]
odp.A
Szczegółowe wyjaśnienie: